Analisis Perilaku Beresiko Tertular COVID-19 - Dwi Safitri, Serly; Ismiati, Ismiati; Patroni, Rini (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2024)
The coronavirus outbreak caused by the SARSCoV2 virus has caused a number of changes in many aspects of people's economic and social life, COVID-19 was officially as a pandemic in March 2020, as it was very easy to spread in the world. Public understanding and awareness of risk behaviors for contracted COVID-19 was still low. It has a huge impact on life, so various methods must be used to fight the virus. The community will play an important role in breaking the chain of transmission of COVID-19 and avoiding the emergence of new sources of transmission. The purpose of this study was to explore in-depth information about the analysis of behavior at risk of contracting COVID-19 in the work area of the puskesmas in the west ring of Bengkulu city. This research used qualitative research methods to explore more in-depth information with in- depth interview techniques. This study used a phenomenological approach to understand the phenomenon in depth to produce data in a descriptive form that was assembled using words with the results of in-depth interviews with informants. The informants in this study were people aged 46-70 years and below who were concerned about behaviors at risk of contracting COVID-19. The results of this study found that the behavior of the elderly people did not used masks because they felt that they did not need to use masks and felt tight or stuffy. The elderly do not know how to use masks properly. Do not wash their hands with soap/handsanitizer because the elderly do not know about washing their hands, never clean their hands when touching their nose and mouth and never wash their hands when touching masks. Not keeping your distance because you don't believe in COVID-19 and not doing COVID-19 protection when visited tourist attractions and worship. The elderly continue to the homes of people who died during the COVID-19 pandemic. COVID-19 Vaccination The elderly do not know about the COVID-19 vaccination, most of whom have not carried out a complete COVID-19 vaccination. It was hoped that health workers and the COVID-19 Task Force can carry out health promotion to the community in the West Circle Health Center Work Area regarding good COVID-19 Infection Behavior.